Tropical soils and crop productivity — A systematic review - Muda , S. A.; Azeez, M. O.; Kehinde, A. D. (ADAN JOURNAL OF AGRICULTURE, 2026)
Tropical soils play a central role in global food production but are characterized by multiple biophysical constraints that limit crop productivity, including low soil organic carbon, nutrient depletion, acidity, erosion, and, in some regions, salinity. These challenges are intensified by heavy rainfall, rapid nutrient leaching, continuous cultivation, and increasing climate variability. This systematic review synthesizes evidence from 287 empirical studies, systematic reviews, and meta-analyses published between 2010 and 2025 to evaluate tropical soil characteristics, degradation processes, and the effectiveness of soil management strategies. Findings revealed that integrated approaches—such as Integrated Nutrient Management (INM), residue retention, cover cropping, conservation agriculture, agroforestry, and targeted amendments including lime, biochar, and phosphate fertilizers—consistently enhance soil fertility, nutrient cycling, microbial activity, and yield stability. However, widespread adoption of these practices is constrained by limited access to inputs, credit, land tenure security, extension services, and labor resources. The review also identifies significant knowledge gaps, particularly the scarcity of long-term trials, limited understanding of soil organic carbon stabilization, and inconsistent performance of emerging amendments. The review suggests that sustainable improvement of tropical soil productivity requires holistic strategies that integrate biophysical innovations with socio-economic and institutional support to strengthen resilience and promote long-term agricultural sustainability.